2011
DOI: 10.1590/s0102-311x2011001400016
|View full text |Cite
|
Sign up to set email alerts
|

Social inequalities and the rise in violent deaths in Salvador, Bahia State, Brazil: 2000-2006

Abstract: Desigualdades sociais e crescimento das mortes violentas em Salvador, Bahia, Brasil: 2000-2006

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
(47 reference statements)
0
8
0
5
Order By: Relevance
“…This divergence in direction of the association agrees with the findings of some review papers Smith, 2002,Rehkopf andBuka, 2006). In the case of homicides, some studies conducted in the United States (Cubbin, et al, 2000), Brazil (Viana, et al, 2011), Great Britain (Shaw, et al, 2005) and Scotland (Leyland and Dundas, 2010) have reported a positive association between homicides and area socioeconomic deprivation. However, it is important to note that few such studies have been conducted in European countries (Laflamme, et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…This divergence in direction of the association agrees with the findings of some review papers Smith, 2002,Rehkopf andBuka, 2006). In the case of homicides, some studies conducted in the United States (Cubbin, et al, 2000), Brazil (Viana, et al, 2011), Great Britain (Shaw, et al, 2005) and Scotland (Leyland and Dundas, 2010) have reported a positive association between homicides and area socioeconomic deprivation. However, it is important to note that few such studies have been conducted in European countries (Laflamme, et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The influence of social determinants on health has been widely discussed by the scientific community [1][2][3] . Some issues suffer major influences from that determination.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the violence stands out for its multifaceted and ambiguous character Homicide mortality rates are considered good indicators to measure the severity of violence in a given population group 4 . Some studies have been conducted in Brazil and in the world to show this relationship 5,6 , however, this approach requires further discussions in northeastern Brazil, where rates grow at an accelerated rate, unlike what happens in other regions, where positive developments were identified in indicators 3,7 .…”
Section: Introductionmentioning
confidence: 99%
“…This is often attributed to rising prosperity combined with roll out of redistributive health and social programmes such as the Bolsa Familia cash transfer programme,30 as well as scaled-up health promotion efforts (especially obesity prevention) 31. Exacerbation of violence-related inequalities has also been observed in one study of adult mortality in Salvador 32. It has been suggested that public health interventions have focused on reducing infectious and chronic diseases but neglect, on the other hand, external causes of ill health such as interpersonal violence.…”
Section: Discussionmentioning
confidence: 99%